Studying the effect of electrodes on the electrical impedance measurement of meat - Dang, Thanh Trung; Nguyen , Phan Kien; Chu Duc Hoang; Nguyen, Thanh Trung (Journal of Military Science and Technology, 2022)
Several investigations contributed to developing the Electrical Resistivity Spectroscopy equipment used to evaluate meat standards. In the prior research, a method for effectively calculating the power resistance spectra of pork meat was devised. This method was successfully implemented. Electrodes fabricated from medical knitting needles and the term means syringes were used in this study to measure the energy-dispersive spectra of flesh. These two different transducers were constructed for the investigation and employed in the measurement process. In medicine, both types of electrodes are utilized; however, assessment findings acquired using the same equipment reveal a distinct disparity between the outcomes of the two measurements. This demonstrates that selecting an electrode for a specific measurement requires careful consideration and consideration overall. In the coming years, the investigation and advancement of weighing electrodes, which are utilized to assess the electronic input resistance of pork meat and over which the research group is concentrating, are further investigated to develop the measurement system electrodes the most appropriate and essential. Using data from knowledge grows.